WEBVTT
00:00:00.510 --> 00:00:03.480
Previously, we learned about the polar form of a complex number.
00:00:04.060 --> 00:00:07.820
This is also known as the trigonometric or modulus argument form.
00:00:08.460 --> 00:00:19.190
We saw how to recognise when the complex number is written in this form and to how to convert between this form and the form π plus ππ, known as the algebraic rectangular or Cartesian form of a complex number.
00:00:19.720 --> 00:00:23.120
But we havenβt seen why we should ever write a complex number in polar form.
00:00:23.160 --> 00:00:25.500
What makes it better than algebraic form?
00:00:26.160 --> 00:00:30.770
The answer or part of the answer is that polar form makes multiplication easy.
00:00:31.410 --> 00:00:33.830
Letβs recap the polar form of a complex number.
00:00:34.300 --> 00:00:40.750
This is π§ equals π times cos π plus π sin π, where π must be greater than or equal to zero.
00:00:41.350 --> 00:00:45.280
With π§ written in this form, we can just read off the modulus and argument.
00:00:45.360 --> 00:00:47.040
Its modulus is the value of π.
00:00:47.170 --> 00:00:48.780
And its argument is the value of π.
00:00:49.330 --> 00:00:53.010
This explains why polar form is also known as modulus-argument form.
00:00:53.930 --> 00:00:56.750
This is best understood using an Argand diagram.
00:00:57.500 --> 00:01:01.240
The modulus π is the distance at the point π§ from the origin zero.
00:01:01.470 --> 00:01:09.070
And the argument π is the measure of the angle that the vector from zero to π§ makes with the positive real axis, when measured counterclockwise.
00:01:09.560 --> 00:01:12.530
Iβd like to show you how the polar form makes multiplication easy.
00:01:12.530 --> 00:01:14.210
So weβre going to need two complex numbers.
00:01:14.510 --> 00:01:31.190
Letβs call this one π§ one then instead of just π§, with modulus π one and argument π one, and introduce the second complex number, π§ two, whose modulus is π two and whose argument is π two, making it π two times cos π two plus π sin π two in polar form.
00:01:31.790 --> 00:01:36.520
Then, it turns out thereβs a very simple expression for the product π§ one π§ two in polar form.
00:01:37.320 --> 00:01:43.660
This is π one π two times cos π one plus π two plus π sin π one plus π two.
00:01:44.490 --> 00:01:48.090
This is in polar form, with a modulus of π one times π two.
00:01:48.620 --> 00:01:52.460
Thatβs the product of the moduluses of π§ one and π§ two.
00:01:53.080 --> 00:02:01.680
And its argument is π one plus π two, which is the sum of the arguments of π§ one and π§ two.
00:02:03.580 --> 00:02:06.650
So we multiply the moduluses but add the arguments.
00:02:07.230 --> 00:02:11.680
This gives a geometric interpretation to the product of complex numbers on an Argand diagram.
00:02:12.540 --> 00:02:16.770
We can think of the effect on π§ one of multiplying by π§ two.
00:02:17.700 --> 00:02:27.410
We end up with a complex number π§ one π§ two, whose modulus is π two times as big as π§ ones and whose argument is π two more than π§ ones.
00:02:28.110 --> 00:02:37.400
Multiplication by π§ two therefore transforms the complex plane by dilation scale factor π two, followed by rotation of π two counterclockwise.
00:02:37.890 --> 00:02:40.910
Itβs beyond the scope of this video to discuss this any further.
00:02:41.100 --> 00:02:49.470
But you might like to think for yourself what happens when π§ two is a positive real number or a negative real number or π or an imaginary number.
00:02:50.480 --> 00:02:54.620
Weβve made this claim about the multiplication of complex numbers in polar form.
00:02:54.740 --> 00:02:56.120
And now we should prove it.
00:02:56.700 --> 00:03:00.520
We do this by first using the expressions for π§ one and π§ two in polar form.
00:03:01.180 --> 00:03:04.610
We can reorder the factors so that π two appears next to π one.
00:03:04.950 --> 00:03:07.740
And now we just have to worry about the terms in parentheses.
00:03:08.030 --> 00:03:11.710
And this is just the multiplication of two complex numbers in the algebraic form.
00:03:12.250 --> 00:03:26.220
We get cos π one cos π two plus π times cos π one sin π two, notice how weβve reordered the factors so that π is at the front, plus π sin π one cos π two plus π squared sin π one sin π two.
00:03:26.610 --> 00:03:28.560
And π squared is negative one.
00:03:29.020 --> 00:03:32.520
So this should be minus sin π one sin π two at the end.
00:03:32.890 --> 00:03:36.250
Using this fact, we can group the real terms and imaginary terms.
00:03:36.580 --> 00:03:43.620
And now, for the main part of the proof, we recognise the real and imaginary parts from the trigonometric angle sum identities.
00:03:44.370 --> 00:03:48.050
The real part is exactly cos π one plus π two.
00:03:49.570 --> 00:03:54.490
And the imaginary part after swapping the terms is just sin of π one plus π two.
00:03:55.090 --> 00:03:57.050
And this is what we had to prove.
00:03:58.170 --> 00:04:03.060
These trigonometric identities seem to come from out of the blue to give us an unexpectedly nice answer.
00:04:03.480 --> 00:04:05.880
We get π§ one times π§ two in polar form.
00:04:05.880 --> 00:04:08.160
And we can read off the modulus and argument.
00:04:08.870 --> 00:04:11.390
The modulus is π one times π two.
00:04:12.150 --> 00:04:15.390
And the argument is π one plus π two.
00:04:16.670 --> 00:04:23.110
Now, if we look back at our claim, we can see that π one was just the modulus of π§ one and π two was the modulus of π§ two.
00:04:23.640 --> 00:04:28.670
So the modulus of π§ one times π§ two is the modulus of π§ one times the modulus of π§ two.
00:04:29.520 --> 00:04:32.390
The modulus of the product is the product of the moduluses.
00:04:32.970 --> 00:04:38.270
And similarly, π one was the argument of π§ one and π two of π§ two.
00:04:38.690 --> 00:04:44.390
So the argument of π§ one times π§ two is the argument of π§ one plus the argument of π§ two.
00:04:45.130 --> 00:04:49.360
And knowing the modulus and argument of this product allows us to write it in polar form.
00:04:49.730 --> 00:04:53.690
So these two facts taken together are equivalent to the claim that we proved.
00:04:54.040 --> 00:04:56.960
And now that we have proved this claim, letβs apply it.
00:04:57.770 --> 00:05:10.160
Given that π§ one equals two times cos π by six plus π sin π by six and π§ two equals one over root three times cos π by three plus π sin π by three, find π§ one times π§ two.
00:05:10.860 --> 00:05:27.630
If π§ one equals π one times cos π one plus π sin π one and π§ two equals π two times cos π two plus π sin π two, then π§ one times π§ two is π one times π two times cos π one plus π two plus π sin π one plus π two.
00:05:28.330 --> 00:05:32.470
Comparing what we have with our formula then, we see that π one is two.
00:05:32.940 --> 00:05:35.910
And π two is one over root three.
00:05:36.360 --> 00:05:40.890
And the modulus of our product, π one times π two, is therefore two times one over root three.
00:05:41.460 --> 00:05:42.660
How about the argument?
00:05:43.040 --> 00:05:46.630
Well, we can see that π one is π by six.
00:05:47.000 --> 00:05:49.610
And π two is π by three.
00:05:50.620 --> 00:05:53.840
Our argument is their sum, π by six plus π by three.
00:05:54.470 --> 00:05:56.200
And now, we just need to simplify.
00:05:56.630 --> 00:05:59.210
Two times one over root three is two over root three.
00:05:59.390 --> 00:06:06.970
And we can rationalise this denominator if we want to by multiplying both numerator and denominator by root three, to get two root three over three.
00:06:07.760 --> 00:06:09.050
How about the argument?
00:06:09.450 --> 00:06:12.070
We can write π by three as two π by six.
00:06:12.300 --> 00:06:15.990
And hence, the argument is three π by six or π by two.
00:06:16.620 --> 00:06:23.850
Making the substitution, we see that the product weβre looking for is two root three over three times cos π by two plus π sin π by two.
00:06:24.520 --> 00:06:29.690
Weβll leave our answer in polar form even though we might know the values of cos π by two and sin π by two.
00:06:30.250 --> 00:06:35.550
And hopefully, having gone through this example, you will agree that multiplying two numbers in polar form is very easy.
00:06:35.680 --> 00:06:39.380
You just have to multiply their moduluses and add their arguments.
00:06:40.030 --> 00:06:43.210
Thatβs less work than multiplying two numbers in the algebraic form.
00:06:44.170 --> 00:06:45.670
Letβs see another example.
00:06:46.430 --> 00:06:58.890
If π§ one equals seven times cos π one plus π sin π one, π§ two equals 16 times cos π two plus π sin π two, and π one plus π two equals π, then what is π§ one times π§ two?
00:06:59.240 --> 00:07:05.660
Well, we know that the modulus of π§ one times π§ two will be the modulus of π§ one, thatβs seven, times the modulus of π§ two.
00:07:05.660 --> 00:07:06.660
Thatβs 16.
00:07:07.260 --> 00:07:10.050
And seven times 16 is 112.
00:07:10.880 --> 00:07:15.810
And we also know that the argument of π§ one times π§ two is the argument of π§ one plus the argument of π§ two.
00:07:16.500 --> 00:07:18.390
The argument of π§ one is π one.
00:07:18.390 --> 00:07:20.520
And the argument of π§ two is π two.
00:07:21.180 --> 00:07:26.950
So this becomes π one plus π two, which weβre told in the question is π.
00:07:27.710 --> 00:07:29.830
Now we know the modulus and argument of this product.
00:07:29.830 --> 00:07:31.970
Itβs easy to write it down in polar form.
00:07:32.720 --> 00:07:39.970
If the modulus of π§ is π and the argument of π§ is π, then we can write π§ in polar form as π times cos π plus π sin π.
00:07:40.820 --> 00:07:43.040
In our case, π is 112.
00:07:43.220 --> 00:07:44.720
And π is π.
00:07:45.210 --> 00:07:50.640
Substituting then, we find that π§ one times π§ two is 112 times cos π plus π sin π.
00:07:51.130 --> 00:07:52.890
This is our answer in polar form.
00:07:53.490 --> 00:07:56.390
We could also write this answer as negative 112.
00:07:56.390 --> 00:07:57.590
That will be acceptable too.
00:07:57.980 --> 00:08:08.500
And we couldβve found this value either by using the fact that cos π is negative one and sin π is zero or by using the fact that if a complex number has an argument of π, that means itβs a negative real number.
00:08:08.950 --> 00:08:14.260
And of course, the only negative real number with modulus 112 is negative 112.
00:08:14.960 --> 00:08:18.700
Weβve seen that using the polar form of the complex number makes multiplication very easy.
00:08:18.820 --> 00:08:20.270
And the same is true for division.
00:08:20.440 --> 00:08:38.510
If π§ one equals π one times cos π one plus π sin π one and π§ two equals π two times cos π two plus π sin π two, then π§ one over π§ two, the quotient of π§ one and π§ two, is π one over π two times cos π one minus π two plus π sin π one minus π two.
00:08:39.390 --> 00:08:44.380
Equivalently, the modulus of a quotient of complex numbers is the quotient of their moduluses.
00:08:44.500 --> 00:08:48.820
And the argument of a quotient of complex numbers is the difference of their arguments.
00:08:49.140 --> 00:08:51.730
And itβs this equivalent statement that weβll prove.
00:08:52.320 --> 00:08:56.860
To prove this, weβll use what we know about the modulus and argument of a product of complex numbers.
00:08:57.460 --> 00:09:03.940
Given two complex numbers, π€ one and π€ two, we know that the modulus of their product is the product of their moduluses.
00:09:04.510 --> 00:09:07.790
And the argument of their product is the sum of their arguments.
00:09:08.510 --> 00:09:09.770
This weβve proved already.
00:09:10.530 --> 00:09:16.560
The key idea of this proof is to let π€ one equal π§ one over π§ two and π€ two equal π§ two.
00:09:17.070 --> 00:09:26.910
Making this substitution, we find that the modulus of π§ one over π§ two times π§ two is the modulus of π§ one over π§ two times the modulus of π§ two.
00:09:27.590 --> 00:09:30.340
And on the left-hand side, the π§ twos cancel.
00:09:30.790 --> 00:09:34.090
And so we get just the modulus of π§ one on the left-hand side.
00:09:34.560 --> 00:09:38.750
And now, we can rearrange this to make the modulus of π§ one over π§ two the subject.
00:09:39.070 --> 00:09:44.490
And when we do this, we find that it is the modulus of π§ one over the modulus of π§ two, as required.
00:09:45.130 --> 00:09:47.200
Now, we just need to do the same for the argument.
00:09:47.630 --> 00:09:59.410
Substituting π§ one over π§ two for π€ one and π§ two for π€ two, we get that the argument of π§ one over π§ two times π§ two is the argument of π§ one over π§ two plus the argument of π§ two.
00:10:00.060 --> 00:10:02.580
And again, the π§ twos on the left-hand side cancel.
00:10:03.010 --> 00:10:05.900
So we get just the argument of π§ one on the left-hand side.
00:10:06.440 --> 00:10:12.550
Rearranging, we find that the argument of π§ one over π§ two is the argument of π§ one minus the argument of π§ two as required.
00:10:13.300 --> 00:10:18.620
Weβve managed to prove this equivalent statement, finding the modulus and argument of our quotient.
00:10:18.900 --> 00:10:24.760
And with this modulus and argument, we can write down the polar form of the quotient π§ one over π§ two.
00:10:25.690 --> 00:10:31.980
This can also be proved like fully multiplication case just by writing the quotient of the two complex numbers in polar form.
00:10:32.600 --> 00:10:36.320
This is more straightforward but involves a lot of algebraic manipulation.
00:10:36.980 --> 00:10:42.410
Anyway, now that weβve seen how we can divide complex numbers in polar form, letβs apply it to some problems.
00:10:43.200 --> 00:10:55.290
Given that π§ one equals 20 times cos π by two plus π sin π by two and π§ two equals four times cos π by six plus π sin π by six, find π§ one over π§ two in polar form.
00:10:56.230 --> 00:11:01.310
Well, we know in general that the modulus of a quotient of complex numbers is the quotient of the moduluses.
00:11:01.660 --> 00:11:03.380
And we can just read off the moduluses.
00:11:03.380 --> 00:11:04.850
They are 20 and four.
00:11:05.340 --> 00:11:09.800
So the of modulus of our quotient is 20 divided by four, which is five.
00:11:10.390 --> 00:11:18.040
And we can use the fact that the argument of a quotient is the difference of the arguments, which in our case are π by two and π by six.
00:11:18.820 --> 00:11:22.160
And we can write π by two over the denominator six.
00:11:22.160 --> 00:11:23.700
Itβs three π by six.
00:11:24.020 --> 00:11:29.060
So the difference is two π by six, which is π by three.
00:11:29.060 --> 00:11:30.790
Thatβs the argument of our quotient.
00:11:31.380 --> 00:11:35.410
Now that we have the modulus and argument, we can write our quotient in polar form.
00:11:36.160 --> 00:11:40.510
π§ one over π§ two is five times cos π by three plus π sin π by three.
00:11:41.080 --> 00:11:49.790
Now, isnβt this much easier than dividing complex numbers in algebraic form, where you have to multiply both numerator and denominator by the complex conjugate of the denominator?
00:11:50.380 --> 00:11:51.180
I think so.
00:11:52.200 --> 00:11:58.350
Given that π§ equals cos seven π over six plus π sin seven π over six, find one over π§.
00:11:59.150 --> 00:12:07.370
Now, we could divide in the way that we divide a complex number in algebraic form, using the complex conjugate of that number to make the denominator real.
00:12:07.860 --> 00:12:09.780
But π§ is also in polar form.
00:12:09.920 --> 00:12:12.400
Its modulus one is not explicitly written.
00:12:12.400 --> 00:12:13.410
But we can write it in.
00:12:14.380 --> 00:12:17.840
And we can see that the argument is seven π by six.
00:12:18.490 --> 00:12:25.990
Now, if you write one in polar form, weβll have a quotient of two complex numbers in polar form, which we know how to evaluate.
00:12:26.600 --> 00:12:28.140
The modulus of one is one.
00:12:28.350 --> 00:12:32.440
And the argument of one and indeed any positive real number is zero.
00:12:33.060 --> 00:12:36.930
So one in polar form is one times cos zero plus π sin zero.
00:12:37.390 --> 00:12:39.320
Now, we have to find the reciprocal of π§.
00:12:39.320 --> 00:12:40.220
Thatβs one over π§.
00:12:40.760 --> 00:12:43.110
And we can write both one and π§ in polar form.
00:12:43.750 --> 00:12:47.430
The modulus of their quotient is then one divided by one, which is one.
00:12:47.930 --> 00:12:50.120
And their argument is the difference of the arguments.
00:12:50.120 --> 00:12:55.390
Thatβs zero minus seven π by six, which is negative seven π by six.
00:12:56.050 --> 00:12:58.640
We donβt need to write the modulus of one explicitly.
00:12:58.640 --> 00:13:04.880
We can just write that one over π§ is cos of negative seven π over six plus π sin of negative seven π over six.
00:13:05.580 --> 00:13:07.070
This is our final answer.
00:13:07.770 --> 00:13:12.700
Weβve seen that using the polar form of complex numbers makes multiplication and division much easier.
00:13:13.000 --> 00:13:14.410
They donβt require as much work.
00:13:15.230 --> 00:13:19.040
However, we havenβt seen how to add or subtract complex numbers in polar form.
00:13:19.590 --> 00:13:27.330
This is because addition and subtraction of complex numbers in polar form is in general much harder than of complex numbers in algebraic form.
00:13:27.880 --> 00:13:36.340
To add two complex numbers in algebraic form, you just add the real parts and the imaginary parts and similarly for subtraction.
00:13:37.060 --> 00:13:38.410
It couldnβt get much easier.
00:13:39.000 --> 00:13:48.510
If you do have to add or subtract complex numbers in polar form, itβs generally best to convert them to algebraic form, before adding or subtracting and then converting back to polar form if required.
00:13:49.400 --> 00:13:53.350
Before the video ends, weβre going to see another operation which polar form makes easier.
00:13:53.680 --> 00:13:57.520
This is exponentiation, which involves finding powers of a complex number.
00:13:58.100 --> 00:14:01.830
This is a bit of a sneak peek of a topic which will be covered in more depth later.
00:14:02.660 --> 00:14:06.720
Consider the complex number π§ equals one plus π root three.
00:14:07.060 --> 00:14:09.430
Our first task is to find the modulus of π§.
00:14:10.150 --> 00:14:11.300
Thatβs straightforward.
00:14:11.300 --> 00:14:14.820
We know that the modulus of π plus ππ is the square root of π squared plus π squared.
00:14:15.310 --> 00:14:23.000
Substituting one for π and root three for π, we get the square root of one plus three, which is the square root of four, which is two.
00:14:23.780 --> 00:14:27.980
Now, for the argument of π§, we see that π§ is in the first quadrant.
00:14:27.980 --> 00:14:30.680
And so its argument π can be found using arctan.
00:14:31.130 --> 00:14:39.330
Substituting again, we find that the argument is arctan root three over one, which a calculator will tell us is π by three.
00:14:39.890 --> 00:14:48.030
Hence, that means using the previous results, use the properties of multiplication of complex numbers in polar form to find the modulus and the argument of π§ cubed.
00:14:49.290 --> 00:14:53.030
Letβs not rush straight to π§ cubed but first consider π§ squared.
00:14:53.580 --> 00:14:55.520
π§ squared is just π§ times π§.
00:14:55.880 --> 00:15:00.470
And we know that the modulus of the product of complex numbers is the product of their moduluses.
00:15:01.560 --> 00:15:06.150
So we find that the modulus of the square of π§ is the modulus of π§ squared.
00:15:06.610 --> 00:15:08.400
How about the argument of π§ times π§?
00:15:08.860 --> 00:15:13.160
This is the argument of π§ plus the argument of π§ or two times the argument of π§.
00:15:14.110 --> 00:15:16.330
Now, weβre ready to consider π§ cubed.
00:15:17.140 --> 00:15:20.760
We use the fact that π§ cubed is π§ times π§ squared.
00:15:21.430 --> 00:15:29.640
And so the modulus of π§ cubed is the modulus of π§ times the modulus of π§ squared, which we know to be the modulus of π§ squared.
00:15:30.140 --> 00:15:36.570
And so we see that the modulus of the cube of a complex number is the cube of the modulus of that complex number.
00:15:37.270 --> 00:15:52.990
To find the argument of π§ cubed, we use the same trick, writing π§ cubed as π§ times π§ squared, using what we know about the argument of a product and the argument of π§ squared, finding that the argument of the cube of a complex number is three times the argument of that complex number.
00:15:53.720 --> 00:15:58.750
Now, we just need to substitute the known values of the modulus of π§ and the argument of π§.
00:15:59.810 --> 00:16:01.700
The modulus of π§ is two.
00:16:02.000 --> 00:16:04.120
So the modulus of π§ cubed is eight.
00:16:04.540 --> 00:16:06.480
And the argument of π§ is π by three.
00:16:07.020 --> 00:16:08.980
So the argument of π§ cubed is π.
00:16:09.680 --> 00:16:12.080
Finally, we find the value of π§ cubed.
00:16:12.840 --> 00:16:15.580
We know the modulus and argument of π§ cubed.
00:16:15.580 --> 00:16:18.070
So we can just write π§ cubed down in polar form.
00:16:18.320 --> 00:16:20.830
Itβs eight times cos π plus π sin π.
00:16:21.370 --> 00:16:27.460
Or using the fact that cos π is negative one and sin π is zero, we could write it as negative eight.
00:16:27.940 --> 00:16:36.660
More interesting than the final answer is what we found on the way to it, those being the expressions for the modulus and argument of π§ cubed.
00:16:37.720 --> 00:16:42.030
This leads to a very compact expression for the cube of the complex number in polar form.
00:16:42.600 --> 00:16:48.250
This is a special case of de Moivreβs theorem, which will be explored in more detail at another time.
00:16:48.840 --> 00:16:51.690
The key points that weβve covered in this video are as follows.
00:16:51.980 --> 00:16:58.240
Calculations involving multiplication and division of complex numbers are often simpler when we work in polar form.
00:16:58.890 --> 00:17:02.590
However, for addition and subtraction, this is definitely not true.
00:17:03.270 --> 00:17:13.840
For complex numbers, π§ one equals π one times cos π one plus π sin π one and π§ two equals π two times cos π two plus π sin π two, the following rules hold.
00:17:14.520 --> 00:17:22.060
Their product, π§ one π§ two, is π one times π two times cos π one plus π two plus π sin π one plus π two.
00:17:23.050 --> 00:17:31.220
And their quotient, π§ one over π§ two, is π one over π two times cos π one minus π two plus π sin π one minus π two.
00:17:32.270 --> 00:17:38.050
From these formulas, we can read off the modulus and argument of a product and quotient of complex numbers.
00:17:38.770 --> 00:17:42.420
The modulus of the product of complex numbers is the product of their moduluses.
00:17:42.600 --> 00:17:46.310
And the argument of the product of complex numbers is the sum of their arguments.
00:17:46.640 --> 00:17:49.950
The modulus of a quotient of complex numbers is the quotient of their moduluses.
00:17:50.130 --> 00:17:53.160
And the argument of the quotient is the difference of the arguments.